Analisis Penentuan Lokasi Potensial Pengembangan Fasilitas Parkir Pada Kawasan Perdagangan Kecamatan Wajo Kota Makassar - Rosmiaty Rosmiaty; Arifuddin Akil; Muhammad Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Wajo District was designated as a trade and service center area in the Makassar City Spatial Plan so that it attracts many visitors and has an impact on increasing parking needs. The problem that occurs is the discovery of parking vehicles on road bodies that violate regulations, such as parking on arterial roads, pedestrian paths, and parking at a distance of less than 25 meters from road intersections, causing traffic flow obstruction on several roads. This study aims to determine potential locations and directions for the development of off-street parking facilities in the trading area by maximizing the limited land area. This study aims to determine the location facilities and direction of off-street parking development in the trading area by maximizing the limited land area. The research location is in Wajo District, Makassar City and was carried out in March-November 2020 (9 months). There are two types of data needed in this study, namely secondary data (data on land availability, land function using RTRW, road crossing points, population density, road size, and number of lanes) and primary data (data on the distribution of parking facilities). Determination of the potential parking location is done with the help of a grid-based ArcGis application. From the results of the grid analysis, it was found that 198 grid units were considered very potential and were divided into five distribution groups. The direction for the development of off-street parking facilities is recommended by implementing a vertical rotary parking system, soul parking system, puzzle parking system, tower parking system, and lift parking system and there is a need for firm action such as imposing ticket and fines for vehicle users who violate statutory regulations shrimp related parking.